2015
DOI: 10.1371/journal.pone.0142527
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Sites of Inhibition of Proteolysis in Pathomimetic Human Breast Cancer Cultures by Light-Activated Ruthenium Compound

Abstract: The cysteine protease cathepsin B has been causally linked to progression and metastasis of breast cancers. We demonstrate inhibition by a dipeptidyl nitrile inhibitor (compound 1) of cathepsin B activity and also of pericellular degradation of dye-quenched collagen IV by living breast cancer cells. To image, localize and quantify collagen IV degradation in real-time we used 3D pathomimetic breast cancer models designed to mimic the in vivo microenvironment of breast cancers. We further report the synthesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 50 publications
0
39
0
2
Order By: Relevance
“…While there was some level of inhibition by 5 in the dark, which was not statistically significant, DQ collagen-I degradation was reduced by over 50% under light conditions. Regarding inhibition in the dark, recent studies with 5 and other nitrile-based inhibitors caged with ruthenium complexes have shown that the caged complexes are less stable in cell growth media than in simple aqueous buffers or DMSO, where half-lives of > 1800 days have been observed, suggesting that some level of inhibitor release may occur under prolonged exposure to cell culture conditions (Respondek et al, 2014; Ramalho et al, 2015). The method used herein represented a significant challenge for our caged complexes, which need to be stable over the course of the assay (48 h) to provide high levels of light control.…”
Section: Discussionmentioning
confidence: 99%
“…While there was some level of inhibition by 5 in the dark, which was not statistically significant, DQ collagen-I degradation was reduced by over 50% under light conditions. Regarding inhibition in the dark, recent studies with 5 and other nitrile-based inhibitors caged with ruthenium complexes have shown that the caged complexes are less stable in cell growth media than in simple aqueous buffers or DMSO, where half-lives of > 1800 days have been observed, suggesting that some level of inhibitor release may occur under prolonged exposure to cell culture conditions (Respondek et al, 2014; Ramalho et al, 2015). The method used herein represented a significant challenge for our caged complexes, which need to be stable over the course of the assay (48 h) to provide high levels of light control.…”
Section: Discussionmentioning
confidence: 99%
“…Data shown are from three independent experiments (48 fields); * ≤0.05; mean ± SD. Adapted from Ramalho et al [10]…”
Section: Figmentioning
confidence: 99%
“…12,33,49 The Ru(bpy) 2 fragment has also been used extensively to cage enzyme inhibitors and small-molecule drugs in live-cell assays. 21,28,34,36,50,51 Apart from Ru(bpy) 2 , Ru(II)-based photocaging groups are frequently composed of bi- or tridentate ancillary ligands, including 2,2′:6′,2″-terpyridine (tpy) and 1,10-phenanthroline (phen). 8,21,28,35,39,52,53 These imine-based photocages have been effectively applied to release bioactive molecules bearing nitriles, thioethers, and aromatic heterocycles, which generally cannot be protected by traditional organic photocages.…”
Section: Introductionmentioning
confidence: 99%